Characterizing the stress and electrical properties of superconducting molybdenum films. (22nd December 2021) - Wang, Yeru; Liang, Yajie; Ding, Jiao; Chen, Naihui; Chen, Yanling; Cui, Wei; Huang, Rui; Li, Chengzhe; Li, Fajun; Liu, Jiejia; Jin, Hai; Wang, Guole; et al.
Abstract: In the process of minimizing stress in sputtered molybdenum (Mo) films for fabricating transition-edge sensor devices, we have investigated correlations between the stress and film deposition parameters. At a fixed sputtering power, the tensile stress of our film samples decreases toward both low and high ends of Ar pressure, suggestive of two physical mechanisms at work: an 'atomic peening' effect at low Ar pressure and the development of voids at high Ar pressure. We have also carried out correlative studies of the stress and electrical properties (including superconducting critical temperature and residual resistivity) of the film samples, and found that the results are complex. We have made extensive comparisons with the published results, and attempted to explain the discrepancies in terms of film deposition techniques, sample preparation and treatment, and dynamical ranges of measurements. It is fairly clear that the microscopic properties, including porosity and disorder, of Mo films may have significant impact on the correlations.